Hypertension and Low Body Weight Are Associated with Depressive Symptoms Only in Females: Findings from the Shika Study - Toru Yanagisawa; Fumihiko Suzuki; Hiromasa Tsujiguchi; Akinori Hara; Sakae Miyagi; Takayuki Kannon; Keita Suzuki; Yukari Shimizu; Thao Thi Thu Nguyen; Fumika Oku; Kuniko Sato; Masaharu Nakamura; et al. (Behavioral Sciences, 2022)
Although the relationship between hypertension and depression is influenced by several physiological factors, including body weight and other lifestyle factors, such as eating behavior, the specific involvement of depression in hypertension remains unclear. Therefore, this epidemiological study examined the role of body weight in the relationship between hypertension and depressive symptoms among the middle-aged and elderly living in the community of Shika town. In total, 1141 males and 1142 females with mean ages of 69.09 and 70.61 years, respectively, participated this study. Physiological factors, including blood pressure, body mass index (BMI), and lifestyle, were investigated in a medical check-up in Shika town. Depressive symptoms were evaluated using the Geriatric Depression Scale 15 (GDS-15). A two-way analysis of covariance exhibited a significant interaction between the two hypertensive groups and body size groups on GDS in females. The post hoc Bonferroni method showed that in the hypertensive groups, GDS was significantly higher in the underweight group (BMI < 18.5) than in the standard/overweight group; however, this relationship was not observed in the no-hypertensive groups. Multiple regression analysis also verified this relationship. Therefore, it is suggested that the combination of hypertension and being underweight is associated with depressive symptoms only in females.